Pengembangan Software Berhitung dalam Pembelajaran Matematika - Lia Septiani (JKPM (Jurnal Kajian Pendidikan Matematika), 2016)
The aim of this research was to develop numeracy software in learning mathematics. The research was conducted on students in class V and VI Elementary School Mangun Jaya 03 and Teratai Putih Global Islamic elementary school and grade VII in State Junior High School 3 South Tambun. The model used to develop the media are ADDIE instructional model. In this research, the product tested to one of the experts in the media, one of the experts in the subject matter of mathematics, one of the experts in instructional design, as well as students of State Elementary School Mangun Jaya 03, Teratai Putih Global Islamic Elementary School and State Junior High School 3 South Tambun divided into three test groups, The trial results media experts with a value of 3.07, which means it has a good criteria. The trial results of mathematical subject matter experts with a value of 3.40, which means it has both criteria, the test results instructional design experts with a value of 3.40, which means having both criteria. While on trial one to one with a value of 3.33, which means it has a good criteria. The trial results of a small group with a value of 3.31, which means it has a good criteria and the results of the trial field test 3,18. Thus the overall average of evaluation experts and test learners have a percentage of 82.04%, which means the numeracy software in learning mathematics named flat calculators and geometry can be categorized either.